2008
DOI: 10.1590/s0103-84782008000500025
|View full text |Cite
|
Sign up to set email alerts
|

Aceturato de diminazeno e dipropionato de imidocarb no controle de infecção por Trypanosoma evansi em Rattus norvegicus infectados experimentalmente

Abstract: RESUMO Este estudo teve como objetivo avaliar o efeito do aceturato de diminazeno e do dipropionato de imidocarb no controle da infecção por Trypanosoma evansi em ratos (Rattus norvegicus) infectados experimentalmente. Cinqüenta e quatro ratos machos foram inoculados via intraperitonial com

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 19 publications
0
5
0
10
Order By: Relevance
“…However, a single dose is not effective for horses, mules and dogs (Tuntasuvan et al 2003;Colpo et al 2005), resulting in lack of efficacy of these drugs (Tuntasuvan et al 2003;Da Silva et al 2008). In addition, the drugs used to treat T. evansi are considered hepatotoxic and nephrotoxic (Spinosa et al 1999), and their prolonged use can cause worsening of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, a single dose is not effective for horses, mules and dogs (Tuntasuvan et al 2003;Colpo et al 2005), resulting in lack of efficacy of these drugs (Tuntasuvan et al 2003;Da Silva et al 2008). In addition, the drugs used to treat T. evansi are considered hepatotoxic and nephrotoxic (Spinosa et al 1999), and their prolonged use can cause worsening of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has investigated in recent years alternative treatments for T. evansi infection because chemotherapy with diminazene aceturate and suramim used in the treatment of trypanosomosis has proved ineffective in many cases (TUNTASUVAN et al, 2003;SILVA et al, 2008b;SILVA et al, 2010). Studies have demonstrated that these drugs have limited effectiveness because they do not cross the blood-brain barrier, thereby creating a potential refuge for trypanosomes during the systemic phase of drug action (JENNINGS et al, 1977;SPINOSA et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A research group has investigated in recent years alternative treatments for T. evansi infection because chemotherapy with diminazene aceturate and suramim used in the treatment of trypanosomosis has proved ineffective in many cases [24,41,42]. Studies have demonstrated that these drugs have limited effectiveness because they do not cross the blood-brain barrier, thereby creating a potential refuge for trypanosomes during the systemic phase of drug action [43,44].…”
Section: Apol1 : a Future Hope For Treatment Of Trypanosoma Evansi Inmentioning
confidence: 99%